The research aimed to overview economic aspect of sustainability small scale fisheries in Tegal district, Central Java. This research used Rapfish method and financial perfonnance analysis To known economic aspect status of sustalnability small scale fisheries In Tegal District. The aim of Research were (1) To describe fisheries sustalnability on small scale fisheriesat Tegal District, Central Java Provlncy, (2) To recommend a policy of fisheries management on small scale fisheries At Tegal Dist - Benny Osta Nababan; Yesi Dewitta Sari; Maman Hermawan (Buletin Ekonomi Perikanan, 2008)
The research aimed to overview economic aspect of sustainability small scale fisheries in Tegal district, Central Java. This research used Rapfish method and financial perfonnance analysis To known economic aspect status of sustalnability small scale fisheries In Tegal District. The aim of Research were (1) To describe fisheries sustalnability on small scale fisheriesat Tegal District, Central Java Provlncy, (2) To recommend a policy of fisheries management on small scale fisheries At Tegal District, Central Java Provincy. The result showed "bundes· and ·jaring rampus· was a Suitable gear to catch fish sustalnabllity, but ·payang gemplo· was not. The research recommend Was it is important to decrease subsidy for small scale fisheries who have undepth fishing ground.